ANALISIS PENGARUH TAMBAHAN KAPUR DAN SEMEN TERHADAP PEMADATAN DAN KUAT TEKAN TANAH SIGAR BENCAH - Zakariya, Rif’an; Fadillah, M. Sadam; Budirahardjo, Slamet; Rizani, Mohammad Debby (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
The soil condition in Sigar Bencah, Semarang City, has characteristics that are less supportive of construction, such as cracks, low bearing capacity, and instability. This study aims to evaluate the effects of soil stabilization using lime and cement on soil compaction and unconfined compressive strength (UCS). The variations of lime and cement content used are 0%, 5%, 10%, and 15%, with lime and cement ratios of 30:70, 50:50, and 70:30. The tests conducted include physical property analysis, standard compaction, and UCS testing. The results of the study show a significant improvement in both UCS and optimal soil compaction after stabilization treatment. The optimal additive combination for improving soil quality was found at a 10% additive content with a 50:50 lime-to-cement ratio, which produced a UCS value of 14.2 kg/cm². This indicates that the use of lime and cement as stabilization materials can enhance soil strength and stability, making it suitable for use in construction in areas with poor soil conditions. This stabilization can also serve as a solution to increase soil bearing capacity, reduce potential damage, and improve soil performance in various construction applications.